2012
DOI: 10.1007/s00380-011-0219-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ouabain on myocardial ultrastructure and cytoskeleton during the development of ventricular hypertrophy

Abstract: The aim of this work is to study cytoskeletal impairment during the development of ouabain-induced ventricular hypertrophy. Male Sprague-Dawley rats were treated with either ouabain or saline. Systolic blood pressure (SBP) was recorded weekly. At the end of the 3rd and 6th week, the rats were killed and cardiac mass index were measured. Hematoxylin-eosin and Sirius red staining were carried out and cardiac ultrastructure were studied using transmission electron microscopy. The mRNA level of Profilin-1, Desmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The sections were then treated with peroxidase‐marked streptavidin/peroxidase before examination under an Olympus microscope (model BX‐51; Tokyo, Japan). We used a semiquantitative scoring system to grade the intensity of the abovementioned immunoreactions. In each glomerulus, positively stained cells were scored according to their staining intensities, which were determined using the following scale: 0 (no staining), +1 (weak but detectable staining), +2 (moderate staining) and +3 (intense staining).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sections were then treated with peroxidase‐marked streptavidin/peroxidase before examination under an Olympus microscope (model BX‐51; Tokyo, Japan). We used a semiquantitative scoring system to grade the intensity of the abovementioned immunoreactions. In each glomerulus, positively stained cells were scored according to their staining intensities, which were determined using the following scale: 0 (no staining), +1 (weak but detectable staining), +2 (moderate staining) and +3 (intense staining).…”
Section: Methodsmentioning
confidence: 99%
“…Data shown are representative of five independent experiments (n = 5). The ADR-treated podocyte in C-G were treated with 0.5 μg/mL ADR for 12 h. ADR, adriamycin; NC, normal control; FITC, fluorescein isothiocyanate; F-actin, filamentous actin semiquantitative scoring system 15,16 to grade the intensity of the abovementioned immunoreactions. In each glomerulus, positively stained cells were scored according to their staining intensities, which were determined using the following scale: 0 (no staining), +1…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…Experimental studies have shown that stimulation of both peripheral (cardiac) and central opioid receptors (ORs) is able to modulate heart function and evoke cardioprotection against ischemia [5][6][7]. The efficacy of opioids in inducing preconditioning and postconditioning not only in intact hearts in vivo [8] but also in isolated cardiomyocytes in vitro [9,10], their inotropic effects [11][12][13], and their impact on growth factor expression [14,15] in cell culture indicate the presence of ORs on cardiomyocytes and not only on neural elements.…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear and cytoplasmic proteins of the HK-2 cells were extracted using a commercially available assay kit (Byotime, Shanghai, China). The total proteins of the HK2 cells and renal cortex were extracted as published previously [ 15 , 16 ]. The protein concentrations were determined using a BCA assay kit (Byotime, Shanghai, China) as instructed.…”
Section: Methodsmentioning
confidence: 99%